2014
DOI: 10.1002/ev.20076
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Capacity to Do and Use Evaluation

Abstract: The construct of organizational evaluation capacity is a concept that is receiving increasing attention in theoretical and research-based literature. It is situated within a stream of inquiry that has come to be known as evaluation capacity building (ECB). This chapter reviews evolving conceptions of ECB and recent research and theory in the area. A conceptualization of organizational capacity for evaluation is explicated. The framework addresses not only the capacity to do but also the capacity to use evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 45 publications
2
86
0
16
Order By: Relevance
“…Nine universities (five public and four private) currently offer master's level training in M&E. International organisations and communities of practice such as MEASURE Evaluation provide platforms for M&E training including self-paced courses, webinars, or live classes. Although these training programmes contribute to the supply side by preparing M&E professionals, research involving multiple organisations across Africa has shown that contents of similar trainings tend to emphasise theory at the expense of practical application and are perceived to have limited practical utility or relevance to trainees' work (Cousins et al 2014b;Tarsilla 2014). These findings are consistent with findings of studies conducted in developed countries (Clinton 2013;SuarezBalcazar & Taylor-Ritzler 2013).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Nine universities (five public and four private) currently offer master's level training in M&E. International organisations and communities of practice such as MEASURE Evaluation provide platforms for M&E training including self-paced courses, webinars, or live classes. Although these training programmes contribute to the supply side by preparing M&E professionals, research involving multiple organisations across Africa has shown that contents of similar trainings tend to emphasise theory at the expense of practical application and are perceived to have limited practical utility or relevance to trainees' work (Cousins et al 2014b;Tarsilla 2014). These findings are consistent with findings of studies conducted in developed countries (Clinton 2013;SuarezBalcazar & Taylor-Ritzler 2013).…”
Section: Introductionsupporting
confidence: 68%
“…There is emphasis on the importance of conceptualising organisational evaluation capacity building (ECB), both in terms of the capacity to do [conduct] evaluation and to use it (Cousins et al 2008(Cousins et al , 2014bHueftle Stockdill, Baizerman & Compton 2002). Briefly, ECB refers to the intentional continuous act of creating and sustaining organisational processes that make doing quality programme evaluation and using it routine within and between organisations (Hueftle Stockdill et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This research domain is called organizational evaluation capacity, or EC, and has gained considerable attention in the last decade (Cousins, Goh, Elliott, & Bourgeois, 2014). EC has been linked to organizational learning and improvement, and is thought to be essential to sustainable evaluation utilization (Alkin & Taut, 2002;Torres & Preskill, 1999;Preskill & Boyle, 2008).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Clearly, there is a variety of issues about which one might make or substantiate decisions or alter attitudes. A fourth purpose, which can either apply to individual people or to the organization as a whole, relates to the explicit development of the capacity to both conduct and use the evaluation process and results (Cousins, Goh, Elliott, & Bourgeois, 2014).…”
Section: Evaluation Usementioning
confidence: 99%